No free love: the dearth of media output from the Architectural Centre in the swinging sixties - Guy, Marriage (Architectural History Aotearoa, 2024)
The Architectural Centre, having made a powerful impact on the design profession in New Zealand in the '40s and '50s, appears to have taken a back seat in the 1960s. Were the drug-crazed psychedelic sixties to blame, or was there still signs of life behind the closed doors? No longer publishing Design Review, the Centre continued to work on projects, mainly behind the scenes, such as the campaign for better town planning in Wellington. The effort that went into this campaign may have led to the Centre having "sucked its bottle dry" and an almost stagnation at times during the 1960s, but in the end achieved its aim with the publication by Wellington's Council of a Town Plan, and the creation of a Town Planning department within the Council. This paper follows the actions of the Centre throughout its "mute" decade, and exposes its continuing influence on the City, on subject matter that is still being discussed today, via the publication of a special supplement in the Dominion, a publishing coup that is unparalleled today.